2013
DOI: 10.1021/cr3002627
|View full text |Cite
|
Sign up to set email alerts
|

Big Signals from Small Particles: Regulation of Cell Signaling Pathways by Nanoparticles

Abstract: Introduction 3391 2. Medical Applications of Nanomaterials 3391 2.1. Use of Nanomaterials in Diagnostic Applications 3392 3. Interaction of Nanomaterials with Living Cells 3392 3.1. Role of Physicochemical NP Properties in the Interaction between NPs and Biological Systems 3393 3.2. NP Uptake into the Cells 3393 3.2.1. Role of Size and Shape in NP Uptake 3393 3.2.2. Role of Surface Charge and Protein Corona on NP Uptake 3395 3.3. Activation of Signal Processing Pathways by NPs 3397 3.3.1. Interaction of NPs wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
123
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(126 citation statements)
references
References 228 publications
1
123
1
1
Order By: Relevance
“…46 Previously, we have observed that mesoporous silicacoated SPIONs had cytotoxic effects on neural progenitor cells (C17.2) when incubated with the particles at a concentration of 10 μg/mL (in iron) for 24 hours (viability: 76.62%±3.26%). 23 Although the cell tolerance of nanomaterials varied with the cell lines, [47][48][49] the improved biocompatibility of i-fmSiO4@SPIONs observed in this study may partially be due to iodinated oil loading, which filled the mesopores on the surface of fmSiO4@SPIONs.…”
mentioning
confidence: 76%
“…46 Previously, we have observed that mesoporous silicacoated SPIONs had cytotoxic effects on neural progenitor cells (C17.2) when incubated with the particles at a concentration of 10 μg/mL (in iron) for 24 hours (viability: 76.62%±3.26%). 23 Although the cell tolerance of nanomaterials varied with the cell lines, [47][48][49] the improved biocompatibility of i-fmSiO4@SPIONs observed in this study may partially be due to iodinated oil loading, which filled the mesopores on the surface of fmSiO4@SPIONs.…”
mentioning
confidence: 76%
“…Possible routes of activation of macrophages towards induced production of inflammatory markers include interaction with receptors on the cell surface, as is documented for nanoparticles, 5 as well as intracellular activation of nuclear transcription factors, 33 e.g. NF--κB.…”
Section: +Particlementioning
confidence: 99%
“…1,5,6 Depending on application, metals, metal oxides, inorganic salts, lipids, polymers and other materials can be formulated into functional materials with sub--micrometer dimensions. Of these, hydrogel nanoparticles are particularly attractive as carriers for biologically fragile cargo 7,8 and as matrices for creation of intracellular sensors 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of the elements of this properties matrix [which includes the Stokes radius, the surface charge (60,61), the density of surface chemical groups (62,63), and the elastic modulus (64), among others] can strongly influence in vivo pharmacokinetics (PK) (i.e., circulation times, uptake within specific cells or within specific organs or disease sites, clearance route, and toxicology) (65,66). In particular, understanding which basic properties of nanomaterials can lead to nonspecific and potentially harmful biological interactions (67)(68)(69) in vivo is a very active field of study. In any case, this matrix of materials properties for optimization represents a sort of "opportunity hurricane" for the scientist or engineer.…”
Section: Inorganic Nanoparticles and Related Nanomaterials In Biomedimentioning
confidence: 99%